Attitudes of Healthcare Workers towards Older People in a Rural Population: A Survey Using the Kogan Scale. (3rd April 2011) - Doherty, Mandy; Mitchell, Elizabeth A.; O'Neill, Siobhan
Abstract : With the global trend towards an increasingly ageing population, it is clear that nurses need to be equipped with the knowledge and skills to fulfil significant roles in responding to future health and support needs. This paper reports the results of a survey that aimed to identify and evaluate the attitudes of nurses, healthcare assistants, and nursing students towards older people. The survey was undertaken in a rural county in the Republic of Ireland. It is reassuring that in our study, we found that these healthcare workers hold positive attitudes towards older people. In addition, we found that study to a higher level at university appears to mitigate towards holding more positive attitudes, and this is an important finding in light of the shift towards nursing as an all-graduate profession.